Nonlinear differential problems with first- or second-order differences in Hilbert spaces - Luca, Rodica (Nonlinear analysis, 2009)
In a real Hilbert space, we investigate the existence, uniqueness and asymptotic properties of the generalized solutions of some nonlinear differential systems with first- or second-order differences, subject to extreme conditions and initial data. Some generalizations of Minty’s theorem for the characterization of maximal monotone operators are also presented.